2007
DOI: 10.1002/ppap.200731911
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Inorganic Hybrid-Polymer Thin Films by PECVD Method and Characterization of Their Electrical and Optical Properties

Abstract: Organic–inorganic hybrid polymer‐like thin films have been deposited on glass and silicon substrates by plasma‐enhanced chemical vapor deposition (PECVD) method using single molecular precursors of the organic–inorganic hybrid polymers. Methylcyclohexane and tetraethylorthosilicate (TEOS) were utilized as organic and inorganic precursors, and hydrogen and Ar (argon) were used as bubbler and carrier gases, respectively. In order to compare the difference between the optical, electrical, and mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Meanwhile, it was shown that the hardness of hybrid plasma polymer was weaker than organic plasma polymer in the same RF power. 15,16) Consequently, the plasma polymer with lower hardness would be easily treated by N 2 APP, resulting in the higher amine group density in the hybrid plasma polymer films. AFM images of the -DNA fixation on the plasma polymer surface, which is realized by the tilting method, are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it was shown that the hardness of hybrid plasma polymer was weaker than organic plasma polymer in the same RF power. 15,16) Consequently, the plasma polymer with lower hardness would be easily treated by N 2 APP, resulting in the higher amine group density in the hybrid plasma polymer films. AFM images of the -DNA fixation on the plasma polymer surface, which is realized by the tilting method, are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Burkey and Gleason attempted to distinguish among mechanical properties ( E = 2–5 GPa, H = 0.2–0.5 GPa) influenced by the duty cycle (2.5–20%) and annealing (400 °C) for plasma polymer films of 1,3,5‐trimethyl‐1,3,5‐trivinylcyclotrisiloxane in a mixture with deionized water deposited at pulsed plasma. A similar study by Bae et al showed a variation of mechanical properties ( E = 4–9 GPa, H = 0.2–0.6 GPa) under the influence of power (20–50 W) and annealing (200–500 °C) for plasma polymer films deposited from a mixture of methylcyclohexane and tetraethylorthosilicate monomers with argon and hydrogen gases. Lee et al deposited plasma polymer films from a mixture of bis‐trimethylsilymethane with oxygen gas; they found that the elastic modulus and hardness increased with the amount of oxygen in the mixture (15–35%), namely 5–9 and 0.4–0.5 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%